A study on clinical and radiological factors for predicting difficult laparoscopic cholecystectomy preoperatively - S., Arun Prasath; Rathnakar, Surag Kajoor; L., Nagaraja Anekal (International Surgery Journal, 2017)
Background: Laparoscopic cholecystectomy considered as the gold standard treatment for symptomatic gall stone disease has 1-13% conversion rate to an open procedure due to various reasons. Present study aims to predict difficult laparoscopic cholecystectomy preoperatively using clinical and sonological factors. Methods: This is a prospective study done on 190 patients who were posted for laparoscopic cholecystectomy from March 2015 to February 2017. Parameters taken into consideration were: age, number of previous attacks of acute cholecystitis, impacted gallstone, thickness of GB wall, pericholecystic fluid collection, history of upper abdominal surgery and obesity. All surgeries were performed by surgeons with minimum ten years of experience on laparoscopic cholecystectomy and ultrasound of the abdomen was performed by senior radiologists with experience of minimum five years. Results: Out of 190 patients, difficulty was experienced in 48 patients of which conversion to open cholecystectomy was needed for 11 patients. Elderly age, multiple attacks of pain abdomen (>2), palpable GB, impacted gallstone, thickness of GB wall >3 mm, peri-GB fluid collection, adhesions due to previous abdominal surgery and obesity were all found to be independent risk factors leading to difficult laparoscopic cholecystectomy. Conclusions: Though there is no definite scoring system to predict difficult LC, there is scope for further refinement to make the same less cumbersome and easier to handle using the above clinical and radiological factors.